The Impact of Elementary School Character Education Programs on Increased Students' Thinking Ability - Artia Sihombing; Azizi Zahwa Norin; Muhammad Dian Perdana; Oktavia Simbolon; Theresia Revani Dianita Silaban; Zhulianty Elisabeth Gultom; Natalia Silalahi (International Journal of Educational Practice and Policy, 2024)
The study is set back by curiosity about whether or not there is an impact of a student's learning method given by an educator in the development of student characteristics. The primary purpose of student characteristic research is to create an optimum learning environment for each student so that they can reach its maximum potential. To meet these demands we analyzed our curiosity by analyzing and observing some elementary school children and phasing information from various sources. From various sources and observations, it is regained that teachers must provide instruction and methods consistent with the needs of learners.